Analysis and critique of two beginning method books for the beginning orchestra classroom - Shipley, Sarah N. (Kansas State University, 2014)
This report gives a detailed description and analysis of two method books used for beginning orchestra classes; Essential Elements for Strings by Michael Allen, Robert Gillespie, and Pamela Tellejohn Hayes, and Strings Basics by Terry Shade and Jeremy Woolstenhulme. Olathe School District #233 in Olathe, Kansas is doing research to decide whether to continue using their current method book, Essential Elements, or switching to a different method book, String Basics, for the 2014-2015 school year. Book 1 from each series is analyzed by looking at the order of concepts taught, how the concepts are introduced, how the book is laid out, illustrations, accompaniment CDs, the teacher’s manual, and additional resources offered by the publishers. The books are then compared and critiqued before a personal recommendation is given on which book would be more beneficial to the students of Olathe.
Keywords: Orchestra; Beginning; Method; Music Education (0522)